Optimization of the magnetic system of a vacuum-arc plasma source with a straight line filter - Aksyonov, D.S.; Vasyliev, V.V.; Luchaninov, A.A.; Strelnitskij, V.E. (Вопросы атомной науки и техники, 2021)
The vacuum-arc plasma source with a rectilinear filter has been optimized for deposition of coatings on large size products. The calculations of the magnetic configuration options of the system were performed by using the FEMM program. New design of the output coil of the filter allows increase by 1.3 times the efficiency of plasma transportation to the substrate with a diameter of 300 mm. Plasma instabilities are proposed for the explanation the features of the motion of vacuum-arc plasma through the regions of an inhomogeneous magnetic field in a rectilinear macroparticles filter with a “magnetic island”. Проведено оптимізацію вакуумно-дугового джерела плазми з прямолінійним фільтром для нанесення покриттів на великогабаритні вироби. Розрахунки варіантів магнітної конфігурації системи проводилися з використанням програми FEMM. Нова конструкція вихідної котушки фільтра дозволяє в 1,3 разa збільшити ефективність транспортування плазми до підкладки діаметром 300 мм. Особливості руху вакуумно-дугової плазми в прямолінійному фільтрі макрочасток з “магнітним островом” пояснюються розвитком плазмових нестійкостей в областях неоднорідного магнітного поля. Вакуумно-дуговой источник плазмы с прямолинейным фильтром оптимизирован для нанесения покрытий на крупногабаритные изделия. Расчеты вариантов магнитной конфигурации системы проводились с использованием программы FEMM. Новая конструкция выходной катушки фильтра позволяет в 1,3 раза увеличить эффективность транспортировки плазмы к подложке диаметром 300 мм. Особенности движения вакуумно-дуговой плазмы в прямолинейном фильтре макрочастиц с “магнитным островом” объясняются развитием плазменных неустойчивостей в областях неоднородного магнитного поля.